Pyrolysis of Low Rank Lignites - Koyun, A.; Yoruc, A. B. Hazar; Erdogan, D. Ceylan; Ahlatcioglu, E. (POLISH ACAD SCIENCES INST PHYSICS, 2013)
In this study, six different Turkish coals were studied. One of them was Zonguldak coal and the others were low rank Turkish lignites. The amount of the pyrolysed gases of the coal as CH4, C3H8, CO, CO2, SO2 were determined from the experiments by using several first order reaction models that include energy distribution and the activation energy distribution during the pyrolysis was calculated at the same time. The results of pyrolysis experiments of coals were examined by means of several first order reaction models that include energy distribution. The tar amounts and overall conversion of six different coals, activation energies of nine volatile components output, standard variation values that belong to their energy distribution, maximum quantity of product of each component and molecular collision coefficients were determined. As a result of using these variables in the model equations, conversion quantities for all of the compounds of six types of coals and variation of activation distribution functions with respect to the kinds of coals were presented graphically with a comparison of the cited data in references. DOI: 10.12693/APhysPolA.123.396
Keywords: COAL; Physics